Cytotoxicity of Vibrio cholerae of Madin Darby bovine kidney cells - Haque, Quazi Manjurul; Mohammad, Najmiyatul Fadilah; Helal Uddin, A.B.M.; Saeed, Mohammad (Faculty of Pharmacy, University of Karachi, 2010)
The cytotoxicity of cell-free culture filtrates of 31 isolates of Vibrio cholerae O1 and O139, 5 reference strains and 26 clinical isolates, was tested on Madin Darby Bovine Kidney (MDBK) cells and Vero cells. The 3-[4,5- dimethylthiazol-2-y]-2, 5-diphenyltetrazolium bromide (MTT) test was used to detect the effect of the filtrates on the proliferation and viability of cultured cell populations. The filtrates were prepared from serial ten-fold dilutions of inoculated AKI and APW broth media with and without the addition of polymyxin B. The APW culture filtrates of both V. cholerae O1 and O139 with and without added polymyxin B showed greater toxicity to MDBK cells as compared to AKI filtrates. The cytotoxicity of AKI-grown V. cholerae O139 to MDBK cells was greater than that of V. cholerae O1 grown in the same medium. The cytotoxicity of APW filtrates on Vero cells was low and only noted when polymyxin was added to the medium. Keywords: Vibrio cholerae, MDBK cells, Vero cells, Cytotoxicity and MTT test.